Soil fertility and organic matter in Vertisol and Ultisol under forest and pasture coverage - Loss, Arcângelo; Pereira, Marcos Gervasio; Bernini, Thiago Andrade; Zatorre, Natália Pereira; Wadt, Paulo Guilherme Salvador (Comunicata Scientiae, 2014)
This study evaluated the changes in soil fertility and soil organic matter (SOM) fractions, afterremoval of the forest and establishment of Urochloa brizantha under Vertisol and Ultisol at Acrestate, Brazil. Samples were collected from soil at depths of 0-5 and 5-10 cm, both under naturalforest and pasture. We quantified soil testing fertility and carbon (C), nitrogen (N) and soil humicsubstances (humin, humic and fulvic acids) contents. We also quantified the particulate organicC (POC), organic carbon associated with soil minerals (OCAM) and carbon oxidizable fractions .Found higher values of Ca, Mg and P in the forest (Vertisol) and pasture (Ultisol). The highest levelsof C and N were observed for (0-5 cm) and forest (5-10 cm), independent of the soil assessed. Thearea of forest showed higher levels of C and N of the humin fraction (Vertisol). Under Ultisol, thispattern was observed in the pasture. The conversion of the area of forest to pasture, even with eightto ten years old, have not restored a balance between the oxidizable fraction C and POC whencompared with the levels recorded in the forest, independent soil evaluated.